On some possibilities of Felwi realization. (19th April 2016) - Oganesyan, Koryun B
Abstract: For a free-electron laser without inversion, estimates of the threshold laser power are found. We calculate the interaction induced deviation angle of electrons in the first undulator. It is shown that for real beams this angle is less than the natural divergence angle of the beam.